Implementasi Undang-undang Nomor 10 Tahun 2009 dalam Pengembangan Kawasan Clungup Mangrove Conservation (CMC) Tiga Warna di Kabupaten Malang - Tri Joko Setyanto; Lalu Rudi Sanjaya; Andin Rusmini (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This research aims to analyze the implementation of Law Number 10 of 2009 concerning Tourism and explore the management steps in the development of the Clungup Mangrove Conservation (CMC) Tiga Warna Area in Malang Regency. Through the establishment of these objectives, it is hoped to provide more specific guidance in achieving progress in the sustainable tourism sector. The development of the tourism sector is the main focus in supporting economic growth and community welfare. To ensure effective management, the Government has enacted Law Number 10 of 2009 concerning Tourism. This law is designed to provide the necessary limitations and guidance to advance the tourism sector. One of the main goals of this law is to create a clear framework and provide necessary guidance to achieve sustainable development in the tourism sector. The research method used is qualitative descriptive, and the conclusion of this study indicates that the CMC Tiga Warna Area has successfully integrated tourism activities with nature conservation and engaged the local community through the non-governmental organization Bhakti Alam Sendang Biru. With an emphasis on conservation and sustainable development aspects, CMC Tiga Warna proves itself as a successful example of the implementation of the Tourism Law, which aims to achieve economic growth, nature preservation, and community welfare.